Supplemental Nutrition Assistance Program Eligibility and HIV Incidence in the United States. (6th March 2021) - Richterman, Aaron; Block, Jason P; Tsai, Alexander C; Ivers, Louise C
Abstract: Background: The connection between food insecurity and HIV outcomes is well established. The Supplemental Nutrition Assistance Program (SNAP), the primary food safety net program in the United States, may have collateral impacts on HIV incidence. "Broad-based categorical eligibility" for SNAP is a policy that provides a mechanism for states to increase the income or asset limits for SNAP eligibility. Methods: We estimated the association between the number of new HIV diagnoses in 2010–2014 for each state and (1) state income limits and (2) state asset limits for SNAP eligibility. We fitted multivariable negative binomial regression models with number of HIV diagnoses specified as the outcome; SNAP policies as the primary explanatory variable of interest; state and year fixed effects; and time-varying covariates related to the costs of food, health care, housing, employment, other SNAP policies, and Temporary Assistance for Needy Families spending. Results: HIV diagnoses within states had a statistically significant association with state income limits for SNAP eligibility (incidence rate ratio [IRR], 0.94 per increase in the income limit by 35% of federal poverty level; 95% CI, 0.91–0.98), but no association with state asset limits (increased asset limit vs no change: IRR, 1.02; 95% CI, 0.94–1.10; eliminated asset limit vs no change: IRR, 1.04; 95% CI, 0.99–1.10). Conclusions: State income limits for SNAP eligibility were inversely associated with the number of new HIV diagnoses for states between 2010 and 2014. Proposals to eliminate the use of broad-based categorical eligibility to increase the income limit for SNAP may undercut efforts to end the HIV epidemic in the United States.